Aqueous extract of kalmegh (andrographis paniculata) leaves as green inhibitor for mild steel in hydrochloric acid solution - Singh, A.; Singh, V.K.; Quraishi, M.A. (My University, 2010)
The inhibition of the corrosion of mild steel in hydrochloric acid solution by the extract of Kalmegh (Andrographis paniculata) leaves extract has been studied using weight loss, electrochemical impedance spectroscopy, linear polarization, and potentiodynamic polarization techniques. Inhibition was found to increase with increasing concentration of the extract. The effect of temperature, immersion time, and acid concentration on the corrosion behavior of mild steel in 1 M HCl with addition of extract was also studied. The inhibition was assumed to occur via adsorption of the inhibitor molecules on the metal surface. The adsorption of the molecules of the extract on the mild steel surface obeyed the Langmuir adsorption isotherm. The protective film formed on the metal surface was analyzed by FTIR spectroscopy. The results obtained showed that the extract of Kalmegh (Andrographis paniculata) leaves extract could serve as an effective inhibitor of the corrosion of mild steel in hydrochloric acid media.
Keywords: Electrochemical impedance spectroscopy; Fourier transform infrared spectroscopy; Andrographis paniculata; Langmuir adsorption isotherms